Do Travel Partners Influence the Emotional Experience of Tourists at Destinations ? A Short Communication - R., Sabari Shankar (Indian Journal of Marketing, 2021)
This short communication is an extract from a major research work on understanding tourists’ experience and post touring behaviour and this portion intended to highlight the role of travel partners in tourists’ emotional experience at a destination. Intensive review of literary sources confirmed that this aspect was untapped and lacked research insights. A structured questionnaire containing the statements measuring tourists’ emotional experience and travel partners was floated to 400 tourists using convenient sampling technique. The data collection instrument also had questions on tourists’ personal factors. Sample size was rounded to 370 after removing the illegible responses. A multivariate analysis approach was employed to test whether travel partners influenced tourists’ emotional experience at a destination. The findings revealed that the emotional aspects such as pleasantness, excitement, calmness, happiness, energetic, friendly, and surprising were influenced by the tourists’ travel partners.